(untitled) (Revista de Ciências Agroveterinárias, 2023)
Camucamuzeiro (Myrciaria dubia), a plant of the Myrtaceae family, is a fruit tree native to the Amazon region, occurring spontaneously in floodplains and on the banks of rivers and lakes. The objective of this work was to quantify the pulp yield and evaluate the morphometric characters of fruits and seeds in camucamuzeiro accessions established as progeny in the Germplasm Collection of Embrapa Amazônia Oriental in Belém, Pará. The physical characterization of the fruits was carried out based on a sample of 1600 fruits harvested from 32 progenies. The fruits were individually characterized according to the following aspects: weight, length, diameter, peel thickness and number of seeds per fruit. Seeds of 10 fruits per treatment were evaluated for weight, length, width and thickness. A completely randomized experimental design was used, with 32 progenies, and then the data. The results showed that the camucamuzeiro fruits have an average weight of 8.15g. The progenies CPATU-83 and CPATU-61 were the ones that stood out in terms of weight, with fruits presenting an average weight of over 11 grams. The average fruit length and diameter were 2.22 cm and 2.39 cm, respectively. The number of seeds averaged 1.92 seeds per fruit. Regarding °Brix, amplitudes of 10.70° and 6.93° occurred in the progenies CPATU-27 and CPATU-28. The pulp percentage of the progenies had an average of 68.70%, being CPATU-54, 62, 23, 24 and 17 statistically higher than the others. The percentage of seeds per fruit showed significant differences with the highest percentage of seeds in CPATU-27, 31 and 30, and the lowest value in fruits of the CPATU-23 plant. The germplasm collection of Embrapa Amazônia Oriental allows the identification of wide genetic variability among progenies of M. dubia. The camucamuzeiro progenies CPATU-17, 23, 24, 54 and 62 showed higher pulp yield.